2012
DOI: 10.1262/jrd.11-092h
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycans Improves Early Development of Zona-free 8-cell Rat Embryos to Blastocysts in a Chemically Defined Medium, but Not the Pregnancy Rate Following Transfer of the Blastocysts

Abstract: Abstract. The objective of the present study was to clarify the possible role of the zona pellucida (ZP) in early development of rat embryos and to determine the effect of glycosaminoglycans on the development of ZP-free 8-cell embryos before or after embryo transfer at the blastocyst stage. Eight-cell embryos were divided into three groups comprised of, 1) intact controls, 2) embryos with the ZP was removed with acidic solution and 3) pairs of ZP-free 8-cell embryos aggregated in a small hollow. These embryos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…These modifications include NHEJ-mediated indels (Kaneko et al, 2014;Hashimoto and Takemoto, 2015;Kaneko and Mashimo, 2015;Qin et al, 2015;Hashimoto et al, 2016;Wang et al, 2016;Remy et al, 2017), large segment deletions (Hashimoto et al, 2016;Wang et al, 2016), conditional KO (Miyasaka et al, 2018), double-KO (Teixeira et al, 2018), HDR-mediated precise nucleotide substitutions (Kaneko and Mashimo, 2015;Qin et al, 2015;Wang et al, 2016) or short sequence insertions using ssODNs (typically < 200 bp) (Hashimoto and Takemoto, 2015;Chen et al, 2016;Wang et al, 2016;Remy et al, 2017) and lsDNA (from 600 bp to 1.5 kb) (Miyasaka et al, 2018). In some studies, electroporation was done in mouse zygotes that were denuded of the zona pellucida (ZP) by a Tyrod's acid treatment (Qin et al, 2015;Chen et al, 2016;Wang et al, 2016), without affecting the early development unlike data reported in rats (Okuyama and Funahashi, 2012). Electroporation also can be applied to mouse and rat frozen zygotes for efficient introduction of CRISPR RNP complexes, without affecting embryo viability or development (Nakagawa et al, 2018;Kaneko and Nakagawa, 2020).…”
Section: Electroporationmentioning
confidence: 99%
“…These modifications include NHEJ-mediated indels (Kaneko et al, 2014;Hashimoto and Takemoto, 2015;Kaneko and Mashimo, 2015;Qin et al, 2015;Hashimoto et al, 2016;Wang et al, 2016;Remy et al, 2017), large segment deletions (Hashimoto et al, 2016;Wang et al, 2016), conditional KO (Miyasaka et al, 2018), double-KO (Teixeira et al, 2018), HDR-mediated precise nucleotide substitutions (Kaneko and Mashimo, 2015;Qin et al, 2015;Wang et al, 2016) or short sequence insertions using ssODNs (typically < 200 bp) (Hashimoto and Takemoto, 2015;Chen et al, 2016;Wang et al, 2016;Remy et al, 2017) and lsDNA (from 600 bp to 1.5 kb) (Miyasaka et al, 2018). In some studies, electroporation was done in mouse zygotes that were denuded of the zona pellucida (ZP) by a Tyrod's acid treatment (Qin et al, 2015;Chen et al, 2016;Wang et al, 2016), without affecting the early development unlike data reported in rats (Okuyama and Funahashi, 2012). Electroporation also can be applied to mouse and rat frozen zygotes for efficient introduction of CRISPR RNP complexes, without affecting embryo viability or development (Nakagawa et al, 2018;Kaneko and Nakagawa, 2020).…”
Section: Electroporationmentioning
confidence: 99%
“…To overcome this physical barrier, the ZP is weakened either by a chemical treatment (Tyrod’s acid) or by application of a strong electric field to create pores. Although the weakening of the ZP allows to better control the electroporation efficiency, many studies have shown that the early developmental potential of zona-free embryos is often compromised, particularly in rats 9 .…”
Section: Introductionmentioning
confidence: 99%